Semen parameters evaluation in men with normal sperm concentration and polyzoospermic men - S. Sh. Khayat; M. V. Andreeva; L. V. Schileyko; T. V. Ostroumova; T. M. Sorokina; D. A. Myasnikov; V. B. Chernykh; L. F. Kurilo (Андрология и генитальная хирургия, 2014)
We analyzed 10 178 semen samples from men in infertile couples within a retrospective clinical study (2007–2012). Basic semen parameters at different sperm concentrations were evaluated, immature germ cells in polyzoospermic men were estimated.